2014
DOI: 10.1097/bpo.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Posttraumatic Cubitus Varus With Corrective Supracondylar Humeral Osteotomies Using the Methyl Methacrylate External Fixator

Abstract: Level IV. Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…When a malunion is present, a choice between accepting the deformity and performing a supracondylar corrective osteotomy must be made. Supracondylar osteotomy for cubitus varus carries a high rate of complications ranging from 7 to 40% [3,12] with mostly unpredictable clinical results [25]. Raney et al reported 68 surgeries for post traumatic cubitus varus.…”
Section: Discussionmentioning
confidence: 99%
“…When a malunion is present, a choice between accepting the deformity and performing a supracondylar corrective osteotomy must be made. Supracondylar osteotomy for cubitus varus carries a high rate of complications ranging from 7 to 40% [3,12] with mostly unpredictable clinical results [25]. Raney et al reported 68 surgeries for post traumatic cubitus varus.…”
Section: Discussionmentioning
confidence: 99%
“…Since the humeral supracondylar wedge osteotomy (HSWO) was first proposed in 1939 [8], it has become the most significant surgical procedure to correct the cubitus varus deformity [9, 10]. However, the focus of the operation is often to correct the varus on the coronal plane, which neglects the sagittal or horizontal deformities and results in the unsatisfactory correction effects [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…There are also several studies reporting promising clinical outcome based on non-surgical methods and external fixators (EFs). [2][3][4] Polymethyl methacrylate (PMMA) has been used as an EF for a long time. It was first reported as an EF in 1972 and first used as an EF together with K wires for hand fractures in 1974.…”
Section: Introductionmentioning
confidence: 99%
“…However, later it was not used as a standard treatment method for long-bone fractures. Recently, Acar et al 2 defined a new external fixation system for corrective supracondylar humeral 1 osteotomies for treatment of posttraumatic cubitus varus deformities using PMMA in children. The main advantages of this system were its low cost and also easy application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation